Gonadotropin-releasing hormone analog therapies for children with central precocious puberty in the United States - Popovic, Jadranka; Geffner, Mitchell E.; Rogol, Alan D.; Silverman, Lawrence A.; Kaplowitz, Paul B.; Mauras, Nelly; Zeitler, Philip; Eugster, Erica A.; Klein, Karen O. (Frontiers in Pediatrics, 2022)
Gonadotropin-releasing hormone agonists (GnRHa’s) are the standard treatment for central precocious puberty (CPP). We aim to present available GnRHa options with a series of easy-to-review tables and discuss factors that influence treatment selection. Five GnRHa’s are currently FDA-approved and prescribed in the US. Published data suggest similar safety and efficacy over the first year of treatment for all FDA-approved GnRHa’s. 1- and 3-month intramuscular (IM) leuprolide acetate (LA) have long-term safety and efficacy data and allow for flexible dosing. 6-month IM triptorelin pamoate offers a longer duration of treatment, but there are no long-term efficacy and outcome data. 6-month subcutaneous (SQ) LA combines a SQ route of injection and long duration of action but lacks long-term efficacy and outcome data. The 12-month SQ histrelin acetate implant avoids injections but requires a minor surgical procedure with local or general anesthesia and offers the longest duration of action. Factors in treatment selection include route of administration, needle size and injection volume, duration of action, and cost. The current GnRHa landscape provides options with varying benefits and risks, allowing physicians and caregivers to select the most appropriate therapy based on the specific needs and concerns of the child and the caregiver. Agents have different advantages and disadvantages for use, with no one agent displaying superiority.